The Effect of a Deep Learning Approach on Students’ Conceptual Understanding and Critical Thinking Skills in Elementary Social Studies Education - Viona Dwi Wulandari; Fauzia Rahma Suci; Yufi Latmini Lasari; Zainal Asril; Afifah Febriani (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2026)
The use of deep learning methods in Social Studies has become a growing approach in elementary schools because it is considered capable of helping students understand concepts more deeply. This study aims to analyze the effect of using deep learning methods on improving students' conceptual understanding and critical thinking skills in Social Studies learning. The study used a mixed methods approach, combining quantitative data through learning achievement tests and qualitative data through observation and interviews. The study sample consisted of 60 students from two classes selected using a cluster sampling technique, while qualitative data were obtained from subject teachers and students involved. Quantitative analysis was conducted using a difference test to observe changes in learning outcomes, while qualitative data were analyzed thematically to describe the process of implementing the method. The results showed that the use of deep learning had a positive effect on improving conceptual understanding and students' ability to relate Social Studies material to real situations. Students appeared more active in providing arguments, processing information, and solving problems. Learning became more focused because the teacher facilitated analysis, in-depth discussions, and reflection. This study has implications that the deep learning method can be applied as an alternative strategy in Social Studies learning in elementary schools to improve the quality of the learning process and outcomes. These findings can form the basis for further research in developing more innovative Social Studies learning designs oriented towards deep understanding.